Book Reviews. Issue 2 (1st October 2015) - Hall, Nick; Mack, Jonathan; Greaves, Ian; Ganguly, Lauhona
Sports on Television: The How and Why Behind What You See, DENNIS Denin ger (2012) New York and Abingdon: Routledge, 236 pp., ISBN: 0415896754, p/bk, $120; ISBN: 041589686, h/bk, $69.95